DIREITO, RELIGIÃO E MORAL ENQUANTO INSTRUMENTOS DE CONTROLE SOCIAL - Reis Friede (TRF2, 2017)
The debate regarding the relation among Law, Religion and Moral has been inspiring the reflection of jurists and philosophers. Notwithstanding the prominence of Law, we must reckon that the complexity of life in society, which generates countless conflicts, could not bestow it the exclusivity of social control. Having in mind the peculiarity of the diverse relations established everyday by the individuals, other mechanisms take responsibility for part of this task. Therefore, the current article analyzes, briefly, Law, Religion and Moral as instruments of social control.